2001
DOI: 10.1002/prot.10024
|View full text |Cite
|
Sign up to set email alerts
|

Design and initial characterization of a circular permuted variant of the potent HIV‐inactivating protein cyanovirin‐N

Abstract: A circular permuted variant of the potent human immunodeficiency virus (HIV)-inactivating protein cyanovirin-N (CV-N) was constructed. New N- and C-termini were introduced into an exposed helical loop, and the original termini were linked using residues of the original loop. Since the three-dimensional structure of wild-type cyanovirin-N is a pseudodimer, the mutant essentially exhibits a swap between the two pseudo-symmetrically related halves. The expressed protein, which accumulates in the insoluble fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The proteins possess identical secondary and tertiary structure, as judged by far- and near-ultraviolet CD spectroscopy (Figure 3). The far-UV CD spectra of the variants were similar to previously-published spectra for wild-type CVN (70). In addition, the intrinsic tryptophan fluorescence emission for each variant was blue-shifted 20 nm compared to the fluorescence of GuaHCl-denatured protein (not shown), indicating the burial of the unique Trp in CVN (Trp49).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The proteins possess identical secondary and tertiary structure, as judged by far- and near-ultraviolet CD spectroscopy (Figure 3). The far-UV CD spectra of the variants were similar to previously-published spectra for wild-type CVN (70). In addition, the intrinsic tryptophan fluorescence emission for each variant was blue-shifted 20 nm compared to the fluorescence of GuaHCl-denatured protein (not shown), indicating the burial of the unique Trp in CVN (Trp49).…”
Section: Resultssupporting
confidence: 82%
“…In addition, other biophysical studies used CVN variants with an additional N-terminal Gly–Ser–His–Met–Gly sequence which remained after thrombin cleavage. CVN containing these additional five animo acids at the N-terminus exhibited anti-HIV activity which is indistinguishable from wild-type protein (10, 69, 70), yet may have thermodynamic properties different from wild type.…”
Section: Resultsmentioning
confidence: 97%
“…The harvested cells were lysed using an EmulsiFlex-C5 (Avestin, Inc.), and the insoluble fraction was resuspended in buffer containing 6 M GnHCl and 10 mM imidazole and centrifuged to remove debris. The solubilized CV-N was then purified under denaturing conditions using a Ni-NTA gravity column (Qiagen) and refolded by dialyzing the Ni-NTA eluate against native buffer overnight at room temperature (42). Following refolding, proteins were additionally purified on a Superdex-75 column and eluted in 25 mM sodium phosphate pH 7.4, 150 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Using residual dipolar couplings, it was shown that dsCV-N has the same overall shape and possibly structure as wild-type CV-N [38]. This construct can also be described as a variation of a circularly-permuted form of CV-N (cpCV-N) in which several residues are shifted in their sequence [12,39]. The monomeric cpCV-N was shown to be moderately less stable than the wild-type CV-N and to display significantly reduced anti-HIV activity.…”
Section: Cvn Mutants and Other Constructsmentioning
confidence: 99%
“…The monomeric cpCV-N was shown to be moderately less stable than the wild-type CV-N and to display significantly reduced anti-HIV activity. Preliminary NMR experiments showed that cpCV-N adopts the same fold as wild-type CV-N, and the determination of a detailed, high-resolution structure is in progress [39].…”
Section: Cvn Mutants and Other Constructsmentioning
confidence: 99%